2021
DOI: 10.1101/2021.08.15.21262077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection with the SARS-CoV-2 Delta Variant is Associated with Higher Infectious Virus Loads Compared to the Alpha Variant in both Unvaccinated and Vaccinated Individuals

Abstract: BackgroundThe emerging SARS-CoV-2 variant of concern (VOC) B.1.6.17.2 (Delta) quickly displaced the B.1.1.7 (Alpha) and is associated with increases in COVID-19 cases nationally. The Delta variant has been associated with greater transmissibility and higher viral RNA loads in both unvaccinated and fully vaccinated individuals. Data is lacking regarding the infectious virus load in Delta infected individuals and how that compares to individuals infected with other SARS-CoV-2 lineages.MethodsWhole genome sequenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
157
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(182 citation statements)
references
References 38 publications
22
157
0
3
Order By: Relevance
“…A study performed in Israel estimated that vaccination with the BNT162b2 (Pfizer/BioNTech) mRNA vaccine substantially reduced the potential for transmission among household contacts 2 . Other recent data have suggested that vaccinated individuals may shed virus (as measured by RTqPCR) at similar levels to unvaccinated individuals, particularly when infected with the Delta variant 35 . Some interpretations of these preliminary studies have suggested that the risk for secondary transmission is similar for vaccinated and unvaccinated individuals.…”
Section: Main Textmentioning
confidence: 92%
“…A study performed in Israel estimated that vaccination with the BNT162b2 (Pfizer/BioNTech) mRNA vaccine substantially reduced the potential for transmission among household contacts 2 . Other recent data have suggested that vaccinated individuals may shed virus (as measured by RTqPCR) at similar levels to unvaccinated individuals, particularly when infected with the Delta variant 35 . Some interpretations of these preliminary studies have suggested that the risk for secondary transmission is similar for vaccinated and unvaccinated individuals.…”
Section: Main Textmentioning
confidence: 92%
“…The Delta variant of concern (VOC) quickly overtook other VOCs (Alpha, Beta, Gamma, Epsilon, Lota) and by late August 2021 accounted for over 98% of new COVID-19 cases in the United States (https://covid.cdc.gov/covid-data-tracker/#variant-proportions). SARS-CoV-2 viral loads are significantly higher in both vaccinated and unvaccinated individuals infected by Delta VOC (1). At least in part this appears to be driven by increased infectivity due to the furin cleavage enhancing P681R mutation (2).…”
Section: Introductionmentioning
confidence: 99%
“…The relative infectiousness of the virus in asymptomatic people is another area of uncertainty in our model projections and this value might shift with emergence of new variants of concern. Our intra-host model was fit to early viral load data from the pandemic and has not been updated for new variants which may have higher viral loads [73][74][75]. Other models with different assumptions fit to separate sets of viral kinetic data well [25,76,77], and may provide slightly different results when considering inter-host transmission probabilities.…”
Section: Discussionmentioning
confidence: 99%